2019
DOI: 10.1186/s12904-019-0428-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of palliative chemotherapy and best supportive care on overall survival and length of hospitalization in patients with incurable Cancer: a 4-year single institution experience in Japan

Abstract: Background This study aimed to analyze the determinants of patients’ choice between palliative chemotherapy and best supportive care (BSC) and to investigate how this choice affects overall survival (OS) and length of hospitalization according to Eastern Cooperative Oncology Group (ECOG) performance status (PS). Methods An oncologist explained the palliative chemotherapy and BSC options to 129 patients with incurable cancer during their first consultation. Data on the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
4
2
Order By: Relevance
“…DFI less than 12 months often symbolizes short-term recurrence, which we speculate may be related to poor treatment [ 22 , 23 ]. In the study of Murakawa et al [ 24 ], the treatment mode is obviously related to OS of tumor patients, which is different from our research results. As for the relationship between PC and poor prognosis of REC patients, we speculate that this may be related to the nonlocality of the lesion range.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…DFI less than 12 months often symbolizes short-term recurrence, which we speculate may be related to poor treatment [ 22 , 23 ]. In the study of Murakawa et al [ 24 ], the treatment mode is obviously related to OS of tumor patients, which is different from our research results. As for the relationship between PC and poor prognosis of REC patients, we speculate that this may be related to the nonlocality of the lesion range.…”
Section: Discussioncontrasting
confidence: 99%
“…DFI less than 12 months often symbolizes short-term recurrence, which we speculate may be related to poor treatment [22,23]. In the study of Murakawa et al [24], the treatment mode is obviously related to OS of tumor patients, which is different from our research results.…”
Section: Discussioncontrasting
confidence: 95%
“…This was not possible to ascertain since no data on performance status existed on the non-PCS patients. We observed that non-PCS patients were less likely to be receiving chemotherapy at referral, and some investigators have shown that patients with poor performance status are less likely to consent to palliative chemotherapy 26 . Thus, one could infer that the reduced use of chemotherapy in the non-PCS group is indicative of worse performance status.…”
Section: Discussionmentioning
confidence: 58%
“…The American Society of Clinical Oncology advocates withholding palliative chemotherapy from patients with solid tumors and an ECOG PS of 3-4, and instead recommends best supportive care (BSC) [4]. However, in our previous study [5], almost half of patients with an ECOG PS of 3-4 selected palliative chemotherapy, while patients with an ECOG PS of 0-2 did not experience prolonged survival with palliative chemotherapy when compared to patients with an ECOG PS of 3-4.…”
Section: Trajectories Of Hospitalization In Three Groups Of Patients mentioning
confidence: 82%